Sources and Rates of Potassium for Drip Irrigation of Polyethylene-mulched Bean Production - Hulu, Versi Putra Jaya; Purnamawati, Heni; Susila, Anas Dinurrohman; Susanto, Slamet (Department of Agronomy and Horticulture, IPB University, 2019)
Common bean is a type of vegetable that can be consumed in the form of young pods. Potassium is one of the macronutrients needed to achieve maximum yield in common bean. Therefore this research is aimed at determining a suitable potassium source as well as an appropriate rate for drip irrigation in common bean using polyethylene mulch. The study was conducted from January to May 2018 at University Farm, IPB University. This experiment was set up as a nested randomized block design with two factors i.e. potassium sources as the main factor ( KCl, ZK, and NPK), and potassium rates (0, 37.5, 75, 112.5, 150 kg of K2O per ha). Fertilizer rates were nested in the main factor and fertilizers were applied Fertilization through a drip irrigation fertigation system with emitters placed close to the roots of plants. Fertilizer sources had significant effects on the variables of growth and bean yields. NPK resulted in a better growth and yield compared with KCl and ZK. Fertilizer sources that have very significant effect were likely related to the shape and solubility of the fertilizers, the ease of application, and also completeness of nutrient content in fertilizer. Based on the pod weight per plot, the productivity per hectare of bean pods produced in this study reached 7.52 ton.ha-1. Potassium (K2O) rate did not have significant effects on the variables of growth and yields of the bean.